Sox on Fish: A New Harm of Overcriminalization - Haugh, Todd (2015)
The harms of overcriminalization are usually thought of in a particular way—that the proliferation of criminal laws leads to increasing and inconsistent criminal enforcement and adjudication. For example, an offender commits an unethical or illegal act and, because of the overwhelming breadth and depth of the criminal law, becomes subject to too much prosecutorial discretion or faces disparate enforcement or punishment. But there is an additional, possibly more pernicious, harm of overcriminalization. Drawing from the fields of criminology and behavioral ethics, this Essay makes the case that overcriminalization actually increases the commission of criminal acts themselves, particularly by white-collar offenders. This occurs because overcriminalization fuels offender rationalizations, which are part of the psychological process necessary for the commission of crime—rationalizations allow offenders to square their self-perception as “good people” with the illegal behavior they are contemplating. Overcriminalization, then, is more than a post-act concern. It is inherently criminogenic because it facilitates some of the most prevalent, and powerful, rationalizations used by would-be offenders. This phenomenon is on display in the recently argued Supreme Court case Yates v. United States. Using Yates as a backdrop, this Essay explores a new way of understanding the detriments of overcriminalization